Design and analysis of a 6 GHz chip antenna on glass substrates for integration with RF/wireless microsystems - Mendes, P. M. (2003)
We report on design and characterization of chip-size antennas for operation at 6 GHz and use in wireless microsystems. Use of a glass substrate and application of wafer-level chipscale packaging (WLCSP) techniques like adhesive wafer bonding and through-wafer electrical via formation, combined with the selected antenna type allows on-chip integration and is the main issue of our work. A short-range wireless link between two systems both equipped with a 11.7x12.4 mm2 patch antenna (measured characteristics: 6 GHz central frequency, 100 MHz bandwidth @ -10 dB, 3 dB gain, 51% efficiency) realized on a Corning Pyrex #7740 glass substrate is demonstrated.